PERBANDINGAN EFEKTIFITAS MEDIA BIOFILTER PECAHAN GENTENG DAN BIOBALL DALAM MENURUNKAN KADAR DETERJEN LIMBAH LAUNDRY - Astrid Retno Hapsari; Hadi Suryono; Pratiwi Hermiyanti (GEMA LINGKUNGAN KESEHATAN, 2016)
Continuous direct discharge of untreated laundry effluent into the streams may cause problems of water pollution and harm to human health. Treatment with biofilter is one chosen among the treatments for the effluent. It had the purpose of comparing the effectiveness of broken roof tiles and bioball as biofilter media in reducing the detergent levels of laundry effluent after aerobic treatment. The study was an analytic experiment using the one-group pretest-posttest design. Methods of analysis to test the differences in the effeciency of reducing detergent levels between broken roof tiles and bioball as biofilter  media combined with activated carbon using statistical test Independent Sample T Test. The parameter to be measured was detergent level by the use of Metylena Blue Active Subtances (MBAs) method.Results showed that the bioball biofilter reactor modified with activated carbon had the largest decrease in the level of detergent in the laundry effluent with efficiency of 1.61% after 160 minutes of flowing. Statistical tests showed that, p = 0,063 so p (sig) 0,05 there was no significant difference in the efficiency of reducing detergent levels for both biofilter media.  Both biofilter media were not effective in reducing the levels of detergent since the effluent remained above the standard value. Utilization of biofilter technology requires a pre-treatment stage, such as coagulation-flocculation due to high levels of pollutants, in order to prevent effluent from polluting surfaces water. In addition, further studies are required which use the acclimatization process and different contact time and biofilter media as well as examining other parameters.   Keywords : Biofilter, Bioball, Broken Roof Tiles, Detergent Levels, Effluent of Laundry